The excavations of Makravank - Grigoryan, Avetis; Mirijanyan, Diana (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Excavations of the 10th-13th centuries monastic complex Makravank included the interior of the nartex and the surroundings of the structure, revealing various details concerning the architecture, cultural setting, and everyday life of the monastery. Along with the excavations, also studies of epigraphic inscriptions and medieval written sources were carried out, the results of which come to complement our knowledge on the history of the monastery.